Quantifying spatial gap patterns in logged over forest in Gunung Basor using Unmanned Aerial Vehicle (UAV) - Abd Khalid, Nurul Ashikin (2020)
Gap refers to open spaces in forest canopies where sunlight penetrates on the forest floor allows new growth. This study aimed to quantify the spatial gap pattern in logged over forest in Gunung Basor using unmanned aerial vehicle (UAV) and to determine the pattern of forest gap such as gap shape, area and distribution. This study found out that when area of gap increased, gap shape tends to be irregular with area ranging from 77 m2 to 90.67 m2 making the gap fraction 14.7%. The number of forest gap recorded highest was 19 when gap area between 0.1 to 4.9 m2. Gaps created by natural disturbances were significantly more numerous, compared to anthropogenic causes such as logging. The Gap Shape Complexity Index (GSCI) value was 0.35 while the largest was 0.86. Vegetative Atmospheric Resistance Index (VARI) of the study area showed that most of the study area was light green in colour indicating existence of forest gaps. The spatial knowledge of the gaps obtained from this study through pattern analysis could be used to link them to certain ecological patterns, such as the creation of gaps, and would eventually assist the relevant authorities to improve their forest management effectively.